2000
DOI: 10.1097/00005650-200002000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Total Quality Management and Organizational Culture on Multiple Outcomes of Care for Coronary Artery Bypass Graft Surgery Patients

Abstract: There was little effect of TQM and organizational culture on multiple endpoints of care for CABG patients. There is a need to examine further the relationships among individual professional skills and motivations, group and microsystem team processes, specifically tailored interventions, and organization-wide culture, decision support processes, and incentives. Assessing the impact of such multifaceted approaches is an important area for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
1
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(180 citation statements)
references
References 21 publications
6
170
1
3
Order By: Relevance
“…Few of these studies, however, examined the effectiveness of hospital QI practices. With few exceptions (e.g., Westphal, Gulati, and Shortell 1997;Shortell et al 2000), most have used perceptual measures of impact or self-reported estimates of cost or clinical impact rather than objectively derived measures of clinical quality (Gilman and Lammers 1995;Shortell et al 1995b). Other multisite, comparative studies have explicitly examined the impact of hospital QI on clinical practice (Carlin, Carlson, and Nordin 1996;O'Connor et al 1996;Gordian and Ballard 1997;Goldberg et al 1998;Ferguson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Few of these studies, however, examined the effectiveness of hospital QI practices. With few exceptions (e.g., Westphal, Gulati, and Shortell 1997;Shortell et al 2000), most have used perceptual measures of impact or self-reported estimates of cost or clinical impact rather than objectively derived measures of clinical quality (Gilman and Lammers 1995;Shortell et al 1995b). Other multisite, comparative studies have explicitly examined the impact of hospital QI on clinical practice (Carlin, Carlson, and Nordin 1996;O'Connor et al 1996;Gordian and Ballard 1997;Goldberg et al 1998;Ferguson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Participation, good communication, conflict resolution, and empowerment were reported to be related to resident outcomes [15,16,[18][19][20][21] . Furthermore, Shortell et al isolated attributes of the work environment and showed that they influence performance in acute hospitals [13,14] and that organizations with positive cultures were more likely to have adopted and internalized continuous quality improvement programs [25] . To achieve both better job satisfaction and quality of care in palliative care, the negative qualities that respondents perceived in the work culture in this study must be minimized, and focus must be given to the qualities that are positive for the work culture.…”
Section: How Do Health Care Personnel At a Pmu Expect The Future Workmentioning
confidence: 99%
“…This is important not only for giving the health care workers empowerment and legitimacy in their working situations but also to avoid stress and burnout [10] . It is important also for the quality of the care in these units because organizations with positive work cultures are more likely to have adopted and internalized continuous quality improvement programs [25] .…”
Section: What Are the Differences Between These Two Perspectives?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the structures, processes, and relationships common to designing, organizing, and implementing hospital quality improvement efforts (Barsness et al, 1993a,b;Blumenthal & Edwards, 1995;Gilman & Lammers, 1995;Shortell et al, 1995bShortell et al, , 2000Weiner, Alexander, & Shortell, 1996, Weiner, Shortell, & Alexander, 1997. These studies indicate that hospitals vary widely in terms of: (1) their approach to implementing QI; (2) the extent to which QI has affected core clinical processes; and (3) the degree to which QI practices have been diffused across clinical areas.…”
Section: Introductionmentioning
confidence: 99%